2014
DOI: 10.3109/00365548.2014.954263
|View full text |Cite
|
Sign up to set email alerts
|

Sputum bacteriology and antibiotic sensitivity patterns of community-acquired pneumonia in hospitalized adult patients in Nigeria: a 5-year multicentre retrospective study

Abstract: Strep. pneumoniae and K. pneumoniae were the most common causes of CAP. The pathogens were most sensitive to levofloxacin and ceftazidime. We suggest that these antibiotics should increasingly be considered as superior options for empirical treatment of CAP in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
6
16
4
Order By: Relevance
“…As a resultin Nigeria, there is a substantial decline in the susceptibility of antibiotics commonly used for empirical treatments.. Examples include 88% of Staphylococcus aureus infections now resistant to methicillin, over 98% resistance to βlactam antibiotics in post-operative wound infections, susceptibility rates below 60% to empiric antibiotics in urinary tract isolates and below 50% for antibiotics used for empiric treatment of patients with community acquired pneumonia [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As a resultin Nigeria, there is a substantial decline in the susceptibility of antibiotics commonly used for empirical treatments.. Examples include 88% of Staphylococcus aureus infections now resistant to methicillin, over 98% resistance to βlactam antibiotics in post-operative wound infections, susceptibility rates below 60% to empiric antibiotics in urinary tract isolates and below 50% for antibiotics used for empiric treatment of patients with community acquired pneumonia [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, quinolone- • The susceptibility of antibiotics commonly used as empirical treatment for many infections in hospitals-especially those of the urinary tract, ear infections and post-operative wound infectionshas declined considerably, e.g. as many as 88 % of Staphylococcus aureus infections are resistant to methicillin (Reardon 2014) • Studies have reported susceptibility rates to empiric antibiotics below 60 % in urinary tract isolates and over 98 % resistance to β-lactam antibiotics in post-operative wound infections (Okesola and Aroundegbe 2011;Muoneke et al 2012;Dibua et al 2014) • Studies have also reported susceptibility rates below 50 % for antibiotics used for empirical treatment of patients with community-acquired pneumonia (Iroezindu et al 2014) South Africa (Mendelson and Matoso 2015) • 50 % of all hospital-acquired S. aureus in public hospitals in 2010 were MRSA, with MRSA accounting for 75 % of all hospital-acquired S. aureus infections in a large tertiary-level paediatric hospital • Enterococcus faecium bloodstream isolates from the private sector showed variable sensitivity to vancomycin, ranging between 33 and 100 % depending on the geographical location • Up to 75 % of K. pneumonia isolated from hospitalised patients were ESBL-producing bacteria • 16 % of carbapenem-susceptible Enterobacteriaceae in the private sector contained a carpapenemase-producing gene, and carpapenemase-producing Enterobacteriaceae are widespread among public hospitals in South Africa Vietnam (Hoa et al 2011; Van Nguyen et al 2013; • Pneumococcal penicillin resistance rates are typically the highest in Asia, with carbapenem-resistant bacteria (notably NDM-1) recently emerging • Streptococcus pneumoniae penicillin resistance rates increased from 8 to 75 % from 1999 to 2007 in Ba Vi, not helped by high rates of self-purchasing of antibiotics (Table 3) • More than 90 % of isolates from principally patients in an intensive care unit in Hanoi tested for resistance to A. baumannii were resistant to tested β-lactamase inhibitors/β-lactamase, carbapenems, cephalosporins, fluoroquinolones and trimethoprim/ sulfamethoxazole. Overall, 25.4 % of isolates were resistant to all tested aminoglycosides, β-lactams and quinolones • There has been a significant increase in resistance of Streptococcus suis to tetracycline and chloramphenicol in isolates between 1997 and 2008, concurrent with an increase in multidrugresistant organisms before courses are finished, cultural differences and underuse due to a lack of access and financial support is seen as key driver of AMR (Llor and Bjerrum 2014;WHO Europe 2014;Klein et al 2015;Laxminarayan et al 2016;Md Rezal et al 2015;Dyar et al 2016).…”
Section: Extent and Threat Of Antimicrobial Resistance And Its Impactmentioning
confidence: 99%
“…The most commonly identified pathogens are Streptococcus pneumoniae, Haemophilus influenzae, atypical bacteria (i.e., Chlamydia pneumoniae, Mycoplasma pneumoniae and Legionella species) and viruses [22,23]. Prognosis is excellent for relatively young or healthy patients.…”
Section: Pathogensmentioning
confidence: 99%